P-type transparent LaCuOS semiconductor synthesized via a novel two-step solid state reaction and sulfurization process. Issue 8 (1st June 2017) - Zhang, Nengduo; Gong, Hao
Abstract: A novel and simple two-step preparation method has been successfully developed to synthesize high quality oxychalcogenide LaCuOS, a direct-gap p-type transparent semiconductor. We first successfully synthesized CuLaO2 using cheap Cu2 O and La2 O3 via solid state reaction, and then achieved high quality LaCuOS through sulfurization at an optimum temperature of 860 °C without using conventional hazardous H2 S or CS2 gas. With the use of easily available and relatively more stable starting materials of Cu2 O, La2 O3 and S, this method is less costly than conventional solid state reaction route for obtaining oxychalcogenides. The synthesized LaCuOS of high purity has a band gap of 3.1 eV and gives a resistivity of 0.25 MΩ cm and high seebeck coefficient of +515 µV/K. Moreover, it demonstrates strong luminescence at room temperature. The success of this novel two-step synthesis method also opens a door for environmental friendly synthesis of other high performance oxychalcogenides.